Reducing energy consumption of prefabricated building elements and lowering the environmental impact of concrete. (15th June 2020) - Sebaibi, Nassim; Boutouil, Mohamed
Highlights: The reducing the carbon footprint of the prefabricated elements. The mechanical performance following the addition of ultrafine cement was better. GGBS is used as a partial substitute for cement, thereby reducing the carbon footprint of the binder. Thermal treatment is used in the prefabrication industry to achieve high strength in concrete at an early age. Abstract: In this study, we attempt to improve the energy efficiency in the precast concrete industry by eliminating thermal treatment and reducing the environmental impact of concrete by using ground granulated blast furnace slag (GGBS) and ultrafine Portland cement (UC). We studied several substitute materials such as UC and GGBS with ultrafine and standard particle fineness values. Thermal treatment is used in the prefabrication industry to achieve concrete with high strength at an early age (~13 h) and allow continuous production. UC was added to study the possibility of eliminating steaming by replacing it with an exothermic reaction generated by the UC. GGBS was used as a partial substitute for cement to reduce the carbon dioxide emission footprint produced by the cement industry. The compressive strength following the addition of UC was encouraging. A 90% evolution at an early age was observed for concrete samples with 42% UC and 42% GGBS with heat treatment. In addition, when using the same composition, a 66% increase was observed without heat treatment. The use of GGBS or fine particles improved the carbon footprint without compromising the compressive behaviour of the concrete.